Social Entrepreneurship and Impact on Community Empowerment in Indonesia's Coastal Areas - Wulan, Titis Sri (IJBLE Scientific Publications Community Inc., 2024)
This study uses quantitative analysis to look at how social entrepreneurship and social initiatives affect community empowerment in Indonesia's coastal regions. Key characteristics were measured using a Likert scale in response to a standardized questionnaire completed by 150 individuals who are involved in social entrepreneurship or initiatives. Data analysis was done using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results show a strong correlation in favor of social entrepreneurship, community empowerment, and social projects. Furthermore, the moderation analysis highlights the significance of stakeholder participation and organizational structure in enhancing the beneficial effects of social initiatives on community empowerment. These findings have implications for social development policy and practice as well as the transformative ability of social entrepreneurship and community-led projects in promoting empowerment within coastal communities.